ChemInform Abstract: Efficient in situ Synthesis of 3, 5‐Disubstituted‐1, 2, 4‐triazoles under Microwave‐Assisted Conditions. Issue 8 (25th February 2014) - Wei, Qing; Qiao, Chengfang; Xia, Zhengqiang; Chen, Sanping
Abstract A concise and high‐yield access to title compounds (II) is achieved by cycloaddition of organonitriles and ammonia under microwave conditions.